The Global Sanctions Data Base - Release 4: The heterogeneous effects of the sanctions on Russia - Erdal Yalçin; Gabriel Felbermayr; Heider Kariem; Aleksandra Kirilakha; Ohyun Kwon; Constantinos Syropoulos; Yoto Yotov (Austrian Institute of Economic Research (WIFO), 2024)
This paper introduces the fourth release of the Global Sanctions Data Base (GSDBR4). Covering the period 1950-2023, it contains 1,547 sanction cases, including the new ones against Russia. The GSDB-R4 comes in two versions, a case-specific and a dyadic one, both freely available upon request at GSDB@drexel.edu. To highlight one of the new features of the GSDB-R4, we combine it with trade data until 2023, and we investigate the effects of the recent sanctions on Russia's trade within an econometric gravity model. We find that, on average, the effects on trade between Russia and the sanctioning countries are negative and statistically significant, but relatively small. We also find that the effects are very heterogeneous across senders, including across the EU members. Finally, our estimates suggest a possible decrease in the direct bilateral trade costs in Russia's bilateral trade with India, China, and Turkey, even after controlling for all possible general equilibrium effects. The implication is that such trade cost decreases may be sufficient to offset the effects of Western sanctions on Russia and even generate net benefits for Russia.
Keywords: F1; F13; F14; F5; F51; H5; N4; 330; Sanctions; Sanctions database; GSDB; Sanctions on Russia